Effect of organic manures and biofertilizers on growth, yield, and quality of turmeric intercropped in arecanut garden - Roy, S.S.; Hore, J.K. (Journal of Plantation Crops, 2011)
The combination of organic manures viz. compost, vermicompost, phosphocompost and mustard cake and microbial inoculants viz. Azospirillum brasilense and Arbuscular mycorrhiza (Glomus fasciculatum) were tried for the organic production of turmeric cv. Suguna grown as intercrop in six years old arecanut cv. Mohitnagar plantation. The experiment was laid out at Horticultural Research Station, Mondouri, BCKV, Nadia, West Bengal in RBD with three replication and eleven treatments for consecutive two years (2005-2006). Compost along with neem cake @ 25 kg and 3.0 kg/palm/year, respectively were applied during pre-monsoon (June) and post-monsoon (September) periods. A significant difference in the rhizome yield was noticed when organic manure-microbial inoculants combination was compared with recommended dose of fertilizers (inorganic). Among the different treatment combinations tried, the most effective treatment was vermicompost + Azospirillum + AM (28.94 t/ha), followed by compost + Azospirillum + AM (26.93 t/ha), as compared to recommended inorganic fertilizers (150:60:150 kg/NPK/ha) (24.11 t/ha). The quality characters such as curcumin and oleoresin content were significantly differed due to organic and biofertilizer combination treatments. Maximum curcumin content (6.71 %) was recorded with compost + Azospirillum + AM followed by vermicompost + Azospirillum + AM (6.46 %) as compared to the lowest curcumin (5.54 %) with phosphocompost + AM. The rhizomes grown with vermicompost + Azospirillum + AM had the highest oleoresin content (11.10 %) followed by compost + Azospirillum + AM (10.83 %). The plants grown with combination of phosphocompost + Azospirillum yielded rhizomes with minimum oleoresin content (9.81 %).